A Review of Domain Modelling and Domain Imaging Techniques in Ferroelectric Crystals - Potnis, P; Tsou, N; Huber, J (2011)
The present paper reviews models of domain structure in ferroelectric crystals, thin films and bulk materials. Common crystal structures in ferroelectric materials are described and the theory of compatible domain patterns is introduced. Applications to multi-rank laminates are presented. Alternative models employing phase-field and related techniques are reviewed. The paper then presents methods of observing ferroelectric domain structure, including optical, polarized light, scanning electron microscopy, X-ray and neutron diffraction, atomic force microscopy and piezo-force microscopy. Use of more than one technique for unambiguous identification of the domain structure is also described.© 2011 by the authors; licensee MDPI, Basel, Switzerland.